Stretch-shortening cycle function of the knee extensor muscle-tendon unit during the power clean - Kipp, K. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this case study was to investigate the stretch-shortening cycle behaviour of the knee extensor muscle-tendon unit during the power clean exercise. Kinematic and kinetic were acquired as a skilled weightlifter performed several repetitions of the power clean at 85% of 1-Repetition Maximum. Knee joint angular velocity, moment, and power time-series during the pull-phase of the power clean were calculated and used to delineate between concentric and eccentric movement phases. The analysis of the kinematic time-series data showed knee extension-flexion-extension movement pattern, whereas the analysis of the kinetic data showed that the movement pattern consisted of dynamic concentric and eccentric sequences, which highlighted stretch-shortening cycle behavior of the knee extensors, and surprisingly also the knee flexor, muscle groups.